History, Culture, and Trade: A Dynamic Gravity Approach - Douglas L. Campbell (Economics and Econometrics Research Institute (EERI), 2010)
What determines trade patterns? Habit persistence in consumer tastes and learning-by-doing in production imply that history and culture matter. Deriving a dynamic gravity equation from a simple model, it is shown that cultural similarity is a product of history, so that trade patterns are a function of bilateral GDP, current trade costs, and the past history of trade costs. Using a trade data set which spans from 1870 to 2000, I demonstrate that many gravity variables operate via lagged trade, that historical trade shocks matter, and that trade patterns are persistent, even across centuries.
Keywords: F10; F12; F22; N70; 330; Dynamic Gravity Equation; Endogenous Preferences; Habit Persistence; Learning By-Doing